Climate change: can we change our horizons? - Sokona, Youba (Technical Centre for Agricultural and Rural Cooperation, 1998)
Drastic changes in the world's climate are predicted over the next few decades. Apparently inevitable, they will force whole countries and cultures in ACP States and beyond to adapt their ways of life, and their agriculture. Yet the reality of...